Measuring sleep in the intensive care unit: Electroencephalogram, actigraphy, or questionnaire?. (February 2020) - Darbyshire, Julie L; Borthwick, Mark; Edmonds, Peter; Vollam, Sarah; Hinton, Lisa; Young, J Duncan
Background: Studies consistently report deranged sleep in patients admitted to intensive care unit. Poor sleep has harmful physical and cognitive effects, and an evidence-based intervention to improve sleep is needed. It is, however, difficult to measure sleep in the intensive care unit. 'Gold standard' monitoring (polysomnography) is unsuitable for usual care. Methods: We collected concurrent sleep data from electroencephalograph recordings, activity monitoring, and nurse- and patient-completed Richards-Campbell Sleep Questionnaires (RCSQ). Results: Electroencephalograph data (n = 34) confirm poor sleep. Individual bouts last approximately 1 min and around 2 h of sleep overnight is common. Correlation between electroencephalograph, self-report, nurse-report, actigraphy and overall activity score is low (ρ = 0.123 (n = 24), 0.127 (n = 22), and 0.402 and − 0.201 (n = 13), respectively). Correlation between nurse and patient assessment is limited (ρ = 0.537 (n = 444)). Conclusions: No current method of sleep monitoring seems suitable in the intensive care unit. However, to facilitate comparison across studies, the patient-completed RCSQ seems the most meaningful measure.